ANALISIS KESULITAN SISWA SMP NEGERI 3 BOLO DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA PADA MATERI SPLDV DITINJAU DARI TAKSONOMI BLOOM DAN RESILIENSI MATEMATIS - Nurul Ismiati; Nurrahmah Nurrahmah; Abdul Haris; Muhammad Yusuf; Arif Rahman Hakim; Muslim Muslim (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT Mathematical problem-solving ability in Two-Variable Linear Equation System (TVLES) word problems remains a major challenge for many students because it requires both Higher Order Thinking Skills (HOTS) and the resilience to cope with learning difficulties. This study aimed to describe students' mathematical problem-solving ability in solving TVLES word problems from the perspective of mathematical resilience. The study employed a qualitative approach with a descriptive-exploratory design. The participants consisted of three ninth-grade students from SMP Negeri 3 Bolo, who were purposively selected to represent high, moderate, and low levels of mathematical resilience. Data were collected through a mathematical problem-solving test, a mathematical resilience questionnaire, semi-structured interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The findings revealed that students with high mathematical resilience were able to complete problem-solving stages more comprehensively than those with moderate and low resilience. The primary difficulties were found in Higher Order Thinking Skills (HOTS), particularly at the analyzing, evaluating, and creating levels of the revised Bloom's Taxonomy. This study concludes that mathematical resilience contributes positively to students' mathematical problem-solving ability. Furthermore, the study provides empirical evidence regarding the relationship between mathematical resilience and problem-solving stages based on the revised Bloom's Taxonomy, which may serve as a foundation for designing more adaptive and meaningful mathematics learning strategies. ABSTRAK Kemampuan pemecahan masalah matematika pada soal cerita Sistem Persamaan Linear Dua Variabel (SPLDV) masih menjadi tantangan bagi banyak siswa karena menuntut penguasaan kemampuan berpikir tingkat tinggi serta ketahanan dalam menghadapi kesulitan belajar. Penelitian ini bertujuan untuk mendeskripsikan kemampuan pemecahan masalah matematika siswa dalam menyelesaikan soal cerita SPLDV ditinjau dari resiliensi matematis. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif-eksploratif. Subjek penelitian terdiri atas tiga siswa kelas IX SMP Negeri 3 Bolo yang dipilih secara purposive untuk mewakili kategori resiliensi matematis tinggi, sedang, dan rendah. Data dikumpulkan melalui tes pemecahan masalah, angket resiliensi matematis, wawancara semi-structured, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa siswa dengan resiliensi matematis tinggi mampu menyelesaikan tahapan pemecahan masalah secara lebih lengkap dibandingkan siswa dengan resiliensi sedang dan rendah. Hambatan utama ditemukan pada kemampuan berpikir tingkat tinggi, terutama pada aspek menganalisis, mengevaluasi, dan mencipta sesuai Taksonomi Bloom revisi. Penelitian ini menyimpulkan bahwa resiliensi matematis berperan dalam mendukung kemampuan pemecahan masalah matematika, sehingga penguatan aspek afektif dan kognitif perlu diintegrasikan dalam pembelajaran matematika untuk meningkatkan kemampuan siswa dalam menyelesaikan soal cerita SPLDV secara lebih efektif dan bermakna.